The fitness of middle age to the elderly based on body mass index and age in the new normal era - Muhammad Akbar Juliansyah; FX Sugiyanto; I Putu Agus Dharma Hita (UIR Press, 2021)
Decrease in physical fitness occurs after the age of 30 years and factors that affect physical fitness include age, gender, BMI, waist circumference, hypertension, and diabetes mellitus. This study aims to determine the physical fitness of middle-aged to elderly people between 45-74 years based on BMI and age. This research is a descriptive study with quantitative methods. The sample of this research is men who are active in badminton activities in Rejang Lebong Regency, which are classified as middle age to elderly people who are taken by purposive sampling. The data collection technique used the BMI test and fitness test. The results show that 1) The average BMI value in middle age to the elderly is 25.47 kg / m2, in the category of light fat. The average value of physical fitness in middle age to the elderly is 33.39, with a very poor category. 2) 26.3% of people have normal nutritional status, 50% of people have mild nutritional status and 23.7% of people have severe nutritional status. 3) 84.2% of people have very poor fitness category, 10.5% of people have poor physical fitness category and 5.3% of people have moderate physical fitness category. So it can be concluded that middle-aged to elderly people with high BMI have less physical fitness and the more middle-aged to elderly people have less physical fitness.